Chronic kidney disease in women: a cross sectional screening in a tertiary care hospital in Varanasi - K, Rai Pradeep; Punam, Rai; Sonam, Bedi (Journal of Clinical Nephrology, 2019)
Background: Chronic Kidney Disease is no longer considered just a health burden today but a major health priority owing to its high treatment costs and poor outcome. World Kidney Day and International Women’s Day in 2018 coincided, thus offering an opportunity to reflect on the importance of women’s health, and specifically their kidney health. The current study aims to identify chronic kidney disease in women through a cross sectional screening in hospital based camp in Varanasi on World Kidney Day. Methods: 138 females attending a health camp were screened for clinical parameters like serum creatinine, random blood sugar, and pregnancy complications. Demographic and anthropometric parameters were noted. Ordinal logistic regression analysis was used to find the predictors of chronic kidney disease stages. Results: The median age of the participants was 36 years. The prevalence of chronic kidney disease was 6.4% with 1.4% of Stage 1, 2.1% of Stage 2, 1.4% of Stage 3 and 1.4% of Stage 4. Women with diabetes were nearly 4 times at a greater risk of developing higher stages of chronic kidney disease compared to women without it. With a unit increase in serum creatinine levels, women were nearly 13 times more likely to develop higher stages of chronic kidney disease. Conclusion: Serum creatinine levels and diabetes were the significant predictors for the development of higher stages of chronic kidney disease. Early screening for kidney diseases in women could reduce the load of health care delivery system that is involved in renal replacement therapies.